Predictors of healthier and more sustainable school travel mode profiles among Hong Kong adolescents - Anthony Barnett; Muhammad Akram; Cindy Hui-Ping Sit; Robin Mellecker; Alison Carver; Ester Cerin (BMC, 2019)
Abstract Background Adolescent travel mode choices to/from school vary in their physical activity (PA) component and environmental sustainability. Research has typically focussed on correlates of active travel, the most healthy and sustainable mode, in comparison to other modes combined. Under the premise that a small shift from less to more healthy/sustainable modes may be a more feasible than a shift to 'pure' active travel (e.g., walking), we examined potential correlates of the odds of undertaking more vs. less healthy/sustainable modes. Methods Hong Kong adolescents attending secondary school and a parent/caregiver (n = 1299 dyads) participated in this cross-sectional study. Latent profile analyses identified groups of adolescents with different transport mode profiles to/from school. Profiles were ranked based on relative PA/sustainability outcomes. Multilevel logistic regression identified environmental, social and psychological factors associated with more vs. less PA/sustainable transport mode profiles to/from school. Results Most frequent transport modes were walking and public transport. Latent profile analysis resulted in a 7-profile model (walk (n = 430); walk & public transport (n = 93); public transport (n = 486); bicycle, car & taxi (n = 60); school bus to & public transport from school (n = 54); school bus (n = 106); car to & car/public transport from school (n = 70)). All profile comparisons were associated with at least one environmental variable. School proximity, access to services and parent transport-related PA were generally associated with higher odds of healthier-more sustainable transport modes. Adolescent-perceived distance and effort barriers to walking and cycling were generally associated with lower odds of more healthy/sustainable modes. Discussion Most adolescents engaged in relatively healthy/sustainable travel modes to/from school. Public transport to walking and school bus to public transport mode shifts are likely to have the biggest impact towards more healthy/sustainable modes. Encouraging parent-related transport PA may positively influence adolescent mode choice. Relatively dense, destination-rich neighbourhoods may encourage more healthy/sustainable transport modes to/from school by providing easy access to schools and services. Conclusion Government policy encouraging enrolment in the closest local school and private school encouragement of public transport rather than school buses may have the greatest impact on shifts to more healthy/sustainable transport modes to/from school in Hong Kong adolescents.